Jam’al-Qur’an Pada Masa Nabi, Khulafa’ Al-Rasyidin, Dan Sesudahnya - Hakmi Hidayat; Sinta Dilla Azizatul Wahidah; Amelia Dea Divanda; Aulia Ghani (CV. ITTC INDONESIA, 2024)
Hadith recording is not always a complex recording of the Qur'an. The Qur'an is the revelation of Allah because it is a book or a sheet of paper that is drawn and written.In order to prevent the Qur'an from drowning into the era, information about the collection of Qur'ân at the time of Khulafaurrasyidin should be disseminated frequently. This is especially true in the digital age, where interpretation is becoming important. Data is collected, read, recorded, and processed. Library data used in this research. This research is descriptive and analytical by analyzing the books of history and the interpretation of the Qur'an. Jam'ul Qur'an comes from the word